Progestin-Inflammatory Cytokine Interactions Affect Matrix Metalloproteinase-1 and -3 Expression in Term Decidual Cells: Implications for Treatment of Chorioamnionitis-Induced Preterm Delivery - Oner, Ceyda (The Endocrine Society, 2008)
Context: Chorioamnionitis (CAM)-elicited preterm delivery (PTD) is associated with elevated amniotic fluid levels of IL-1β and TNF-α. We hypothesized that IL-1β and TNF-α may induce matrix metalloproteinase (MMP)-1 and MMP-3 activity to promote PTD by degrading decidual and fetal membranes and cervical extracellular matrix. Objective: Our objective was to evaluate: 1) MMP-1 and MMP-3 expression in decidual sections from uncomplicated term, idiopathic preterm, and CAM-complicated deliveries, and 2) the separate and interactive effects of IL-1β, TNF-α, medroxyprogesterone acetate (MPA), and a p38 MAPK inhibitor (SB203580) on MMP-1 and MMP-3 expression in term decidual cells (DCs). Interventions and Main Outcome Measures: Decidua were immunostained for MMP-1 and MMP-3. Cultured term DCs were incubated with estradiol (E2) or E2 plus MPA with or without IL-1β or TNF-α with or without SB203580. ELISA and Western blotting assessed secreted MMP-1 and MMP-3 levels, quantitative real-time RT-PCR assessed mRNA levels, and substrate gel zymography was used to determined MMP-1 and MMP-3 proteolytic activity. Results: MMP-1 and MMP-3 immunostaining was more prominent in CAM-complicated decidua vs. control preterm and term decidual specimens (P < 0.05). Compared with basal outputs by DCs incubated with E2, TNF-α enhanced MMP-1 and MMP-3 secretion by 14 ± 3- and 9 ± 2-fold, respectively, and IL-1β increased MMP-1 and MMP-3 secretion by 13 ± 3- and 19 ± 2-fold, respectively (P < 0.05). Addition of MPA lowered basal MMP-1 and MMP-3 outputs by 70%, whereas the TNF-α- and IL-1β-enhanced MMP-1 and MMP-3 levels were blunted by more than 50% (P < 0.05). SB203580 suppressed TNF-α- and IL-1β-induced MMP-1 and MMP-3 secretion by severalfold. Western blotting confirmed the ELISA results, and mRNA levels corresponded with MMP-1 and MMP-3 protein levels. MMP-1 and MMP-3 proteolytic activity was confirmed by substrate gel zymography. Conclusion: Augmented DC-expressed MMP-1 and MMP-3 in CAM-complicated pregnancies may promote PTD via decidual, fetal membrane, and cervical extracellular matrix degradation. Effects of progestin-p38 MAPK signaling inhibition on cytokine-enhanced MMP-1 and MMP-3 expression in term DCs suggest alternative mechanisms to prevent CAM-induced PTD.